2022
DOI: 10.1002/prp2.961
|View full text |Cite
|
Sign up to set email alerts
|

Association of income and educational levels with adherence to direct oral anticoagulant therapy in patients with incident atrial fibrillation: A Finnish nationwide cohort study

Abstract: Low socioeconomic status has been associated with poor outcomes in patients with atrial fibrillation (AF). However, little is known about socioeconomic disparities in adherence to stroke prevention with direct oral anticoagulants (DOACs). We assessed the hypothesis that AF patients with higher income or educational levels have better adherence to DOACs in terms of treatment implementation and persistence. The used nationwide registry‐based FinACAF cohort covers all patients with incident AF starting DOACs in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
(96 reference statements)
1
7
0
Order By: Relevance
“…20 Therefore, ensuring timely and equitable referral of women, individuals from UREG, and those with adverse SDOH for rhythm control therapy is important. In patients with AF, indicators of lower socioeconomic status were associated with lower oral anticoagulation rates, 21 lower rate of adherence during direct oral anticoagulant (DOAC) initiation, 22 specialty care, 21,23 and less use of cardioversion 4,21 and catheter ablation. 4,21,24 Indicators of socioeconomic disadvantages, such as increased risk of hospitalization, 25 stroke, 4,21 HF, 4,21,26 and death, were also associated with complications in patients with AF.…”
Section: Background and Pathophysiologymentioning
confidence: 99%
“…20 Therefore, ensuring timely and equitable referral of women, individuals from UREG, and those with adverse SDOH for rhythm control therapy is important. In patients with AF, indicators of lower socioeconomic status were associated with lower oral anticoagulation rates, 21 lower rate of adherence during direct oral anticoagulant (DOAC) initiation, 22 specialty care, 21,23 and less use of cardioversion 4,21 and catheter ablation. 4,21,24 Indicators of socioeconomic disadvantages, such as increased risk of hospitalization, 25 stroke, 4,21 HF, 4,21,26 and death, were also associated with complications in patients with AF.…”
Section: Background and Pathophysiologymentioning
confidence: 99%
“…Cost of medication and follow-up of OAC can influence the prescription rates. 25 , 26 Unequal access to OAC in socioeconomically disadvantaged patients and different geographical areas have been shown in previous studies. 26 In a study by Llorca and colleagues, 25 those living in more socioeconomically deprived and rural areas had lower OAC prescription rates.…”
Section: Discussionmentioning
confidence: 64%
“… 25 , 26 Unequal access to OAC in socioeconomically disadvantaged patients and different geographical areas have been shown in previous studies. 26 In a study by Llorca and colleagues, 25 those living in more socioeconomically deprived and rural areas had lower OAC prescription rates. Moreover, previous studies by Essien and colleagues 27 , 28 showed lower initiation of OAC for Black patients and lower DOAC use for Black and Hispanic patients.…”
Section: Discussionmentioning
confidence: 64%
“…Several methods for estimating adherence are available. Medication refill adherence may be obtained through health administrative claim databases using the proportion of days covered (PDC) or medication possession ratio (MPR), and patients with PDC or MPR ≥ 0.80–0.90 are defined as adherent [ 165 ]. Self-reported adherence may be obtained through interviews with questionnaires.…”
Section: Adherence To Oral Anticoagulant Intakementioning
confidence: 99%
“…Socioeconomic status, income, and educational levels do not seem to be associated with medication adherence [ 191 , 203 ]. However, in the nationwide registry-based FinACAF cohort, covering 74,222 adults with AF on DOACs, higher income or education has been associated with adherence to DOACs (OR 1.18 (1.12–1.25) and 1.21 (1.15–1.27), respectively) [ 165 ].…”
Section: Socioeconomic Status and Educationmentioning
confidence: 99%